"HOT" Alkaline Hydrolysis of Amorphous MOF Microspheres to Produce Ultrastable Bimetal Hydroxide Electrode with Boosted Cycling Stability. Issue 49 (21st October 2019) - Zhang, Haobing; Xu, Ben; Mei, Hao; Mei, Yingjie; Zhang, Shiyu; Yang, Zhendong; Xiao, Zhenyu; Kang, Wenpei; Sun, Daofeng
Abstract: Nickel/cobalt hydroxide is a promising battery‐type electrode material for supercapacitors. However, its low cycle stability hinders further applications. Herein, Ni0.7 Co0.3 (OH)2 core–shell microspheres exhibiting extreme‐prolonged cycling life are successfully synthesized, employing Ni‐Co‐metal–organic framework (MOF) as the precursor/template and a specific hydrolysis strategy. The Ni‐Co‐MOF and KOH aqueous solution are separated and heated to 120 °C before mixing, rather than mixing before heating. Through this hydrolysis strategy, no MOF residual exists in the product, contributing to close stacking of the hydroxide nanoflakes to generate Ni0.7 Co0.3 (OH)2 microspheres with a robust core–shell structure. The electrode material exhibits high specific capacity (945 C g −1 at 0.5 A g −1 ) and unprecedented cycling performance (100% after 10 000 cycles). The fabricated asymmetric supercapacitor delivers an energy density of 40.14 Wh kg −1 at a power density of 400.56 W kg −1 and excellent cycling stability (100% after 20 000 cycles). As far as is known, it is the best cycling performance for pure Ni/Co(OH)2 . Abstract : An amorphous metal–organic framework template/precursor and KOH aqueous solution are separately heated and mixed until 120 °C to produce hydroxide electrodes. The electrode obtained through this unique "HOT" alkaline is extremely stable during cycling. Furthermore, the low KOH concentration of 0.2 m and recycled ligands during the unique "HOT" alkaline treatment are preferable for practical applications.